"Bad to the Bone": Reading Revelation Rooned - Cadwallader, Alan H. (Australian biblical review, 2018)
The homogenisation of the language of the Bible in the course of its translation shows out especially in the book of Revelation. Various apologetic devices are used to explain or excuse the problems in the Greek of the author but the most successful actually occurs in translation, where the problems disappear. This paper is a call for a bad translation of the book, that is, a translation that actually reflects the problems that occur in the Greek text. It raise the issues that would need to be addressed in the course of making such a translation, both internal to the text and also the issues of negotiating a comparative context that might inform the register of that translation. It then looks at two examples.